Learning quality innovation through integration of pedagogical skill and adaptive technology - Huda M.; Hashim A.; Teh K.S.M.; Shankar K.; Ayshwarya B.; Nguyen P.T.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
This paper aims to explore the modern learning environment (MLE) which may emerge from the secondary education into the tertiary education. This integration usually derives from enhancing the pedagogical skill and adaptive technology to strengthen the teaching and learning process. Literature review from referred books and journals was conducted with thematic analysis. The investigation was employed in depth analysis from referred books, journals and conferences using the keywords of pedagogical skill and adaptive technology and modern learning environment. The multiple finding from met-synthesis was conducted by searching for the information which is organised using substantive keywords. The findings reveal that the role of MLE can be divided into attempting to perform learning quality, integrating the learning with continuous process, making easy in getting the sources, creating flexibility in learning. This study is expected to contribute the way of maintaining inside factor within the human being which is significantly necessary to make effort in assisting spirit performance in teaching process. To assist students across learning environment by pedagogical skills with encouraging higher teaching and learning, making convince into the pedagogy might be necessary a way to promote a range of pedagogical skills continuing integration with technological tools. In addition, using experience to boost the abstract ideas acquired in certain subjects as the source of knowledge itself can become a particular principle for the enhancement of learning in higher education. Blue Eyes Intelligence Engineering & Sciences Publication.